Tinjauan Yuridis Pertanggungjawaban Pidana Korupsi Pengadaan Alat Kesehatan Rsud Sidikalang : Studi Putusan Pengadilan Negeri Medan No. 61/Pid.Sus-Tpk/2016/PN-Mdn - Rendra Alfonso Sitorus; Syafruddin Kalo; Mahmul Siregar; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Abstract.Bank Indonesia states that there are 3 (three) problems inhibiting the economic growth in Indonesia. Firstly, Indonesia lags behind in infrastructure; secondly, there is inefficiency in bureaucracy; and thirdly, corruption. Highest priority has been put on corruption to be overcome by Indonesians. Since the corruption in Indonesia has been systematical and widespread, not only does it financially harm the financial condition of the country, but it also extensively violates people’s social and economic rights. The practice of corruption may take place anywhere, such as in the public institutions, private institutes, and in daily life. KPK (the Corruption Eradication Committee) has recorded that the country has endured financial loss more than IDR 1 trillion due to corruptions in good and serviceprocurement. One of the regencies that procures goods and service is Dairi Regency i.e. the medical equipment procurement in Sidikalang Hospital, Dairi, pursuant to the Ruling of Medan District Court with Case No.61/Pid.Sus-TPK/2016/PN.Mdn pronounced to have financially harmed the country for IDR 551,357,374.- The results of the research demonstrate that the legal regulations on procurement of goods and service in Indonesia are divided into 3 (three) large parts, namely: (a) the Period of the Presidential Decree Number 80/2003 and its amendments, (b) the Period of Presidential Regulations Number 54/2010 and its amendments, and (c) the Period of Presidential Regulations Number 16//2018. The Legal status and authority of related parties in the Procurement of the Medical Equipment in Sidikalang Hospital is that the Director of Sidikalang Hospital as the Budget User is authorized to use the budget. NM as the Commitment Making Officer is liable for the execution of the procurement of goods/service. The legal consideration in the criminal act of corruption in the procurement of the medical equipment in Sidikalang Hospital based on the Ruling of Medan District Court Number 61/Pid.Sus-TPK/2016/PN.Mdn is that the decision is made after firstly distinguishing the element of “against the law” in article 2 paragraph (1) of Law on Acting Technical Implementation Officer from the element of “power abuse” in article 3 of Law on Acting Technical Implementation Officer. However, in the judge’s consideration, the qualificationof the defendant is not specified and accurate, so that it is difficult to accept the logic of the sentence. On the other hand, the panel of Judges has failed to present the defendant’s role which raises a question; whether the sentence is worth the faults and the defendant’s role in a quo case even though the judge pronounces lighter sentence than the prosecutors’ demands. Keywords: criminal act of corruption, government’s good/service procurement, penal liabilities